Geometric Accuracy and Mechanical Behavior of PA6 Composite Curved Tubes Fabricated by Fused Filament Fabrication (FFF). Issue 7 (17th May 2022) - Shirinbayan, Mohammadali; Benfriha, Khaled; Tcharkhtchi, Abbas
Abstract : Herein, the effect of processing parameters including infill pattern and reinforcement type on the dimensional accuracy of products manufactured by the fused filament fabrication (FFF) process as well as the mechanical performance is studied. The reinforcements used to manufacture the PA6 composite are carbon, Kevlar, and glass fibers. The compression properties of the stated composites are compared. The results show that the rectangular fill pattern is less deformed compared with triangular, hexagonal, and solid ones. However, the compression strength is decreased by changing the infill pattern from the solid infill to hexagonal, triangular, and rectangular. Although there is no significant difference in terms of compression behavior, the printed PA6 reinforced with carbon fiber which is deformed outward contrary to Kevlar and glass fibers, which are deformed inward. Finally, the results confirm that the selection of the appropriate types of reinforcements and infill patterns among the several available types during the printing process is effective in improving the mechanical properties and also in providing better geometrical quality of the surfaces and the consequent dimensional precision improvement of the parts printed by the FFF process. Abstract : Herein, the effect of processing parameters on the dimensional accuracy of products manufactured by the fused filament fabrication (FFF) process as well as the mechanical performance is assessed. The rectangular fill pattern is less deformed compared with triangular, hexagonal, and solid ones. The compression strength is decreased by changing infill pattern from the solid infill to hexagonal, triangular, and rectangular.